The role of communication and investment in physical culture and sports as components of a healthy lifestyle - Yaroslav Leonov; Oleksandr Lohvynenko; Tetyana Lohvynenko; Anatolii Kharakhaichuk; Tetyana Kuryllo (Sport TK)
Regular physical exercise is linked to improved health, longevity, and a lower risk of chronic diseases. This study explores the role of communication in promoting a healthy lifestyle through the popularisation of physical culture and sports, and examines the economic impact of such activities. It investigates how communication contributes to promoting a healthy lifestyle through sports and the effectiveness of investments in these areas. The study employed theoretical research methods, including analysis, systematisation, and generalisation of contemporary literature. Sports significantly impact the economies of numerous countries, driving substantial financial investments and employing large workforces. Effective communication is crucial for entrepreneurship in sports, as it enables the creation of strong networks and media engagement, providing essential information for better decision-making. Startups that blend communication and economic strategies have become increasingly popular, with examples like FuboTV, Dream11, and SeatGeek demonstrating success. Investments in professional sports teams are distinctive due to risks such as unpredictable outcomes and fluctuating stock prices. Fans, often small shareholders, tend to prioritize a team’s long-term goals over immediate profit. Additionally, some companies invest in sports not just for financial returns, but also to boost brand recognition and increase product sales.